Professional Preparation of the Teacher for the New Ukrainian Elementary School - Voitovych, Anna (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article covers to the actual problems of vocational training of the future teacher of the primary school in the context of reforming the education system in Ukraine. Considerable attention is paid to the socio-cultural component in the pedagogical process of a higher educational institution, as well as the issues of standardization of education. The author emphasizes that dynamic social processes, the phenomenon of globalization, the need for formation of a civil society, fostering of national consciousness and identity determine the interest of the public in the described issues, first of all for teaching. The theoretical aspects of teacher training for creation of socio-cultural educational environment of the primary school, the realization of possibilities of socio-cultural mobility and others are substantiated. It is proved that socio-cultural mobility of a teacher, which is closely connected with the process of professionalization, implies active activity according to the adapting and accepting the values of a socio-cultural environment. It was emphasized on the need to prepare future specialists of primary education for the purposive socio-cultural upbringing of children